2020
DOI: 10.3389/fimmu.2020.581370
|View full text |Cite
|
Sign up to set email alerts
|

Dsg2 Upregulation as a Rescue Mechanism in Pemphigus

Abstract: In pemphigus vulgaris (PV), autoantibodies directed against the desmosomal cadherin desmoglein (Dsg) 3 cause loss of intercellular adhesion. It is known that Dsg3 interactions are directly inhibited by autoantibody binding and that Dsg2 is upregulated in epidermis of PV patients. Here, we investigated whether heterophilic Dsg2-Dsg3 interactions occur and would modulate PV pathogenesis. Dsg2 was upregulated in PV patients' biopsies and in a human ex vivo pemphigus skin model. Immunoprecipitation and cell-free a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
10
0
3
Order By: Relevance
“…Moreover, in cultured keratinocytes it was shown that expression of Dsg2 ( 221 ) similar to Dsg1 ( 332 ) was protective against anti-Dsg3-antibody-induced loss of adhesion. Because Dsg2 can undergo heterophilic interaction with Dsg3, which is less sensitive to direct inhibition of autoantibodies targeting Dsg3, it is possible that Dsg2 up-regulation is supporting to maintain cell adhesion in PV ( 333 ).…”
Section: Rescue Pathways In Pemphigus Such As Dsg2 and Camp Upregulationmentioning
confidence: 99%
“…Moreover, in cultured keratinocytes it was shown that expression of Dsg2 ( 221 ) similar to Dsg1 ( 332 ) was protective against anti-Dsg3-antibody-induced loss of adhesion. Because Dsg2 can undergo heterophilic interaction with Dsg3, which is less sensitive to direct inhibition of autoantibodies targeting Dsg3, it is possible that Dsg2 up-regulation is supporting to maintain cell adhesion in PV ( 333 ).…”
Section: Rescue Pathways In Pemphigus Such As Dsg2 and Camp Upregulationmentioning
confidence: 99%
“…Murine keratinocytes from JUP S665A mice strain were generated as described in detail before 56,69 . In short, epidermis of neonatal mice were removed using Dispase II (Sigma-Aldrich, Munich, Germany) and epidermal cells were isolated by treatment with Accutase (Sigma-Aldrich) for 1 h. Cells were seeded in complete FAD media (0,05 mM CaCl 2 , PAN Biotech, Aidenbach, Germany) on flasks coated with collagen I (rat tail; BD Bioscience, New Jersey, US).…”
Section: Methodsmentioning
confidence: 99%
“…34,35 Depois, Hartlieb et al (2014) demonstraram que, embora a Dsg2 contribua menos do que -197 -a Dsg3 para a coesão dos queratinócitos, a Dsg2 compensou a perda de função da Dsg3. 6,36 Mais recentemente, Sigmund et al (2020) demonstraram que a Dsg2 faz ligação heterofílica com a Dsg3 e pode minimizar a perda de adesão entre os queratinócitos no processo da acantólise. 37 Somando os nossos resultados aos relatos da literatura, a superexpressão da Dsg2 na PI e em amostras de mucosa do PF e PV parece estar em consonância com todos os relatos mencionados: a superexpressão da Dsg2, para compensar a perda de função das Dsg1 e Dsg3, poderia proteger o processo da acantólise e estar envolvida na reparação tecidual.…”
Section: Discussionunclassified
“…6,36 Mais recentemente, Sigmund et al (2020) demonstraram que a Dsg2 faz ligação heterofílica com a Dsg3 e pode minimizar a perda de adesão entre os queratinócitos no processo da acantólise. 37 Somando os nossos resultados aos relatos da literatura, a superexpressão da Dsg2 na PI e em amostras de mucosa do PF e PV parece estar em consonância com todos os relatos mencionados: a superexpressão da Dsg2, para compensar a perda de função das Dsg1 e Dsg3, poderia proteger o processo da acantólise e estar envolvida na reparação tecidual. Ainda, a hiperexpressão da Dsg2 em todas as camadas da epiderme na PI e PL do PF e PV poderia justificar a produção de autoanticorpos contra a Dsg2 pelo fenômeno de epitope-spreading.…”
Section: Discussionunclassified
See 1 more Smart Citation